2019
DOI: 10.1155/2019/6984845
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Transferase P1 Polymorphism Might Be a Risk Determinant in Heart Failure

Abstract: Disturbed redox balance in heart failure (HF) might contribute to impairment of cardiac function, by oxidative damage, or by regulation of cell signaling. The role of polymorphism in glutathione transferases (GSTs), involved both in antioxidant defense and in regulation of apoptotic signaling pathways in HF, has been proposed. We aimed to determine whether GST genotypes exhibit differential risk effects between coronary artery disease (CAD) and idiopathic dilated cardiomyopathy (IDC) in HF patients. GSTA1, GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The significance of the G2M pathway is relevant to the LVNC since many stress-responsive genes often play a role in heart development and pathogenesis ( 30 ). The glutathione-S-Transferase pi 1 (GSTP1) gene is highly polymorphic and involved in many diseases including cancer and heart failure ( 31 ). Its role in LVNC could be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of the G2M pathway is relevant to the LVNC since many stress-responsive genes often play a role in heart development and pathogenesis ( 30 ). The glutathione-S-Transferase pi 1 (GSTP1) gene is highly polymorphic and involved in many diseases including cancer and heart failure ( 31 ). Its role in LVNC could be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all members of the GST family exhibit genetic polymorphisms, which can result in a complete lack or reduction of enzyme activity [38] . Two genetic variants in the GSTP1 gene have been shown to confer altered catalytic and noncatalytic activity [39] . These are the GSTP1 * G allele (rs1695), encoding a protein in which amino acid isoleucine (Ile) is substituted with valine (Val) at position 105, and the GSTP1 * allele (rs1138272), in which alanine (Ala) is substituted with (Val) at position 114.…”
Section: Discussionmentioning
confidence: 99%
“…These are the GSTP1 * G allele (rs1695), encoding a protein in which amino acid isoleucine (Ile) is substituted with valine (Val) at position 105, and the GSTP1 * allele (rs1138272), in which alanine (Ala) is substituted with (Val) at position 114. Simeunovic et al [39] reported that the GSTP1 G allele (rs1695) was significantly associated with an increase in the levels of soluble intracellular adhesion molecule-1 (ICAM-1) in patients with heart failure. In an animal study, NSAID induced a rapid increase in ICAM-1 expression in blood vessels, probably because of inhibition of prostaglandin synthesis [40] .…”
Section: Discussionmentioning
confidence: 99%
“…GO [76], SLC16A9 [77], ACADSB (acyl-CoA dehydrogenase short/branched chain) [78], IMPA1 [79], CD300LG [80], CIRBP (cold inducible RNA binding protein) [81], PIK3R1 [82], YEATS4 [83], USP2 [84], NEDD9 [85], CHCHD5 [86] and ERAP1 [87] promotes hypertension. HSPB1 [88], CRYAB (crystallin alpha B) [89], ANXA5 [90], CCR2 [91], RGS4 [92], TNFRSF1A [93], XBP1 [94], NKX2-5 [95], NEU1 [96], GSTP1 [97], COMT (catechol-O-methyltransferase) [98], LIMK1 [99], CAMKK1 [100], CD276 [101], SMARCA4 [102], ADORA2B [103], ACOT1 [104], RGN (regucalcin) [105], PPA2 [106], KAT2B [107], PDK1 [108], CS (citrate synthase)…”
Section: Discussionmentioning
confidence: 99%